1988
DOI: 10.1002/ar.1092200202
|View full text |Cite
|
Sign up to set email alerts
|

Human lumbar zygapophyseal joint inferior recess synovial folds: A light microscope examination

Abstract: The structure of human lumbar zygapophyseal joint inferior recess synovial folds as seen by high-power light microscopy is described. Small paravascular nerves and nerves unrelated to blood vessels are demonstrated in the synovial folds. Elastic fibres are demonstrated in the interlocular fibrous septa of the synovial tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…9,[15][16][17][18] In addition, anatomic studies of the lumbar spine using computed tomography and MRI have visualized meniscoids in the lumbar spine. 19 -21 Yu et al 12 were able to depict meniscoids in the cervical spine in anatomic specimens with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…9,[15][16][17][18] In addition, anatomic studies of the lumbar spine using computed tomography and MRI have visualized meniscoids in the lumbar spine. 19 -21 Yu et al 12 were able to depict meniscoids in the cervical spine in anatomic specimens with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although the TMJs are modified fibrous joints and the Z joints are planar synovial joints, the same mechanism is reasonable for the Z joints, because the Z joints have an ample synovium found not only along the inner joint capsule but also surrounding the Z joint synovial folds. 20,21 Further research is required to verify the source of Z joint intra-articular ADH. Additional work characterizing the ultrastructural and biochemical composition of the ADH is also warranted.…”
Section: Nature and Source Of Adhmentioning
confidence: 99%
“…3 3 , and 6B,C) may be a sequel to "nipping" between the articulating surfaces (Kos and Wolf, 1972). Giles (1988) has suggested that the abundance of elastic fibres demonstrated within the multilobulated synovial folds may impart a potential for elastic recoil to minimize the possibility of these synovial folds becoming trapped during normal joint movements. In a small number of cases the hyaline cartilage did not completely cover the facet surfaces, and the adjacent non-articular area was occupied by a fibroadipose synovial fold (Fig.…”
Section: Discussionmentioning
confidence: 99%